PENGARUH INOKULASI MIKORIZA ARBUSKULA TERHADAP PERTUMBUHAN BIBIT TANAMAN SLOW GROWING (GLODOKAN DAN TANJUNG - Reza Dimas Putra; Delvian Delvian; Deni Elfiati (Peronema Forestry Science Journal, 2016)
This research aims to find out the response or effect of arbuscular mycorrhizal inoculation on growth of slow growing plant. This research was conducted in the greenhouse of the Faculty of Agriculture, University of North Sumatra, Medan.This research uses completely randomized factorial design with 2 factors namely mycorrhizal doses (0 g / seed, 5 g / seed, 10 g / seed, and 15 g / seeds) and plant species (glodokan and tanjung). Parameters measured were plant height, plant diameter, leaf number, percentage of root colonization, P uptake, total dry weight, and short root ratio. The results showed the interaction between plant species and dose mycorrhizal not significantly affected all parameters of eachs treatment. Conversely single factor plant species showed significant effect on all parameters of each treatment, but to a single factor dose of mycorrhizal significant effect on the total dry weight and P uptake but no significant effect on the parameters of height, diameter, number of leaves, the ratio of the root crown and root colonization. Different types of plants  will give a different response to growth.Keywords: Mycorrhizal Fungi, Tanjung, Glodokan, Marginal Land